Effect of bile acid on anorectal function in man. Issue 3 (March 1989) - Edwards, C A; Brown, S; Baxter, A J; Bannister, J J; Read, N W
Abstract : The effects of rectal infusions (500 ml) of deoxycholic acid (1 mmol/l, 3 mmol/l) or normal saline on basal anorectal motility and responses to rectal distension were studied in 11 normal volunteers. Deoxycholic acid (1 mmol/l) did not alter anorectal motor patterns under basal conditions but reduced the rectal volumes required to induce a desire to defecate (deoxycholic acid 76 (12) ml v saline 123 (12) ml; mean (SEM) p less than 0.01), and to produce anal relaxation (deoxycholic acid 83 (14) ml v saline 152 (24) ml; p less than 0.05) and perception of the rectal balloon (deoxycholic acid 56 (10) ml v saline 104 (17) ml; p less than 0.01) that were sustained for the period of distension (1 min). Seven of 10 subjects could not tolerate an infusion of 3 mmol/l deoxycholic acid. Between two and 30 minutes after the start of the infusion they experienced an extreme urge to defecate which was associated with large amplitude pressure waves in the rectal channels (amplitude 30 (5) mmHg, duration 0.7 (0.1) min, frequency 1.7 (0.4)/min). Such contractions were never seen during saline infusion. Thus, rectal infusion of deoxycholic acid at physiological concentrations increases the sensitivity of the rectum to distension, and promotes an urgent desire to defecate in normal subjects.